Marker free model-based radiostereometric analysis for evaluation of hip joint kinematics: A validation study. Issue 6 (June 2018) - Hansen, L.; De Raedt, S.; Jørgensen, P. B.; Mygind-Klavsen, B.; Kaptein, B.; Stilling, M.
Abstract : Objectives: To validate the precision of digitally reconstructed radiograph (DRR) radiostereometric analysis (RSA) and the model-based method (MBM) RSA with respect to benchmark marker-based (MM) RSA for evaluation of kinematics in the native hip joint. Methods: Seven human cadaveric hemipelves were CT scanned and bone models were segmented. Tantalum beads were placed in the pelvis and proximal femoral bone. RSA recordings of the hips were performed during flexion, adduction and internal rotation. Stereoradiographic recordings were all analyzed with DRR, MBM and MM. Migration results for the MBM and DRR with respect to MM were compared. Precision was assessed as systematic bias (mean difference) and random variation (Pitman's test for equal variance). Results: A total of 288 dynamic RSA images were analyzed. Systematic bias for DRR and MBM with respect to MM in translations (p < 0.018 mm) and rotations (p < 0.009°) were approximately 0. Pitman's test showed lower random variation in all degrees of freedom for DRR compared with MBM (p < 0.001). Conclusion: Systematic error was approximately 0 for both DRR or MBM. However, precision of DRR was statistically significantly better than MBM. Since DRR does not require marker insertion it can be used for investigation of preoperative hip kinematics in comparison with the postoperative results after joint preserving hip surgery. Cite this article : L. Hansen, S. De Raedt, P. B. Jørgensen, B. Mygind-Klavsen, B. Kaptein, M. Stilling. Marker free model-based radiostereometric analysis for evaluation of hip joint kinematics: A validation study. Bone Joint Res 2018;7:379–387. DOI: 10.1302/2046-3758.76.BJR-2017-0268.R1.